Ethylene mediated physiological response for in vitro development of salinity tolerant tomato. Issue 1 (1st January 2020) - Rao, Yalaga Rama; Ansari, Mohammad Wahid; Singh, Anil Kumar; Bharti, Niharika; Rani, Varsha; Verma, Amit; Gupta, Ramwant; Sahoo, Ranjan Kumar; Siddiqui, Zahid Hameed; Abbas, Zahid Khorshid; Bains, Gurdeep; Brajendra,; et al.
ABSTRACT: Tomato is an important crop and has immense health benefits and medicinal value. Here, we described how salinity stress affects tomato plant growth and developmental processes and productivity. It causes ionic toxicity, oxidative damage, osmotic stress, and hormonal imbalance. In this review, we emphasized the crucial role of ethylene (ET) towards in vitro development of tomato crop by mediating stress response, particularly high salt. There are evidences that salinity stress modulates the expression of ACS and beta-CAS, which leads to ET and cyanide accumulation. We draw attention to how ET negatively or positively mediates salinity stress response by maintaining endogenous biomolecules, Na + /K + ion balance and redox homeostasis. How ET inhibitors and polyamines as protectants reverse the negative effects of ET/salinity stress-induced cellular damage by cross talk with important physiological processes-photosynthesis and respiratory and salt overly sensitive (SOS). The literature appraised herein will contribute to a better understanding of the development of salinity stress tolerant tomato.